How Artificial Intelligence Has Impacted Accounting: A Systematic Literature Review - Rika Apriana; Armiani Armiani (International Journal of Economics, Management and Accounting, 2025)
This article demonstrates the broad and deep integration between artificial intelligence technology and accounting. It presents the results of a literature review of various scientific articles on artificial intelligence and accounting. This review uses various international article sources to reach more widely about artificial intelligence in accounting. Artificial intelligence comes with various novelties. Where the novelty of this intelligence will have a positive or negative impact and provide challenges and opportunities in accounting for both academics, practitioners, and policymakers.